2018
DOI: 10.5194/acp-18-10881-2018
|View full text |Cite
|
Sign up to set email alerts
|

Polar stratospheric cloud climatology based on CALIPSO spaceborne lidar measurements from 2006 to 2017

Abstract: Abstract. The Cloud-Aerosol Lidar with Orthogonal Polarization (CALIOP) on the CALIPSO (Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observations) satellite has been observing polar stratospheric clouds (PSCs) from mid-June 2006 until the present. The spaceborne lidar profiles PSCs with unprecedented spatial (5 km horizontal × 180 m vertical) resolution and its dual-polarization capability enables classification of PSCs according to composition. Nearly coincident Aura Microwave Limb Sounder (MLS) meas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
131
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(169 citation statements)
references
References 102 publications
(97 reference statements)
13
131
1
Order By: Relevance
“…In the Max simulation the ICE PSCs lasted until mid-March. CALIPSO (Pitts et al, 2007(Pitts et al, , 2018Spang et al, 2018) also observed PSCs in the 2010/2011 winter. The observed ICE PSC areas are comparable to the Fin- Figure 5.…”
Section: Polar Stratospheric Cloudsmentioning
confidence: 92%
“…In the Max simulation the ICE PSCs lasted until mid-March. CALIPSO (Pitts et al, 2007(Pitts et al, , 2018Spang et al, 2018) also observed PSCs in the 2010/2011 winter. The observed ICE PSC areas are comparable to the Fin- Figure 5.…”
Section: Polar Stratospheric Cloudsmentioning
confidence: 92%
“…There is a large variability in observed NAT number densities (e.g. Pitts et al, 2011;Spang et al, 2018;Pitts et al, 2018) and choosing a particular number constitutes a simplification. However, assuming higher number densities for NAT leads to larger NAT surface areas (Drdla and M€ uller, 2012) and thus to a larger heterogeneous reactivity on NAT.…”
Section: Resultsmentioning
confidence: 99%
“…The left and middle columns of Figure show MLS gas‐phase HNO 3 observations at the pressure (altitude) levels of 31 hPa (~22 km) and 46 hPa (~20 km). These are the altitudes where PSCs, HNO 3 sequestration, and denitrification are typically found in the Arctic (Pitts et al, ; Waibel et al, ). In the right column, we show MIPAS observations at 20 km, where NAT particles are expected to grow to large sizes during gravitational settling (Carslaw et al, ; Fahey et al, ).…”
Section: Complementary Mipas and Mls Observationsmentioning
confidence: 99%